2022
DOI: 10.3390/atmos13050727
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Impact of the New ECMWF Multi-Layer Snow Scheme

Abstract: The representation of snow is a crucial aspect of land-surface modelling, as it has a strong influence on energy and water balances. Snow schemes with multiple layers have been shown to better describe the snowpack evolution and bring improvements to soil freezing and some hydrological processes. In this paper, the wider hydrological impact of the multi-layer snow scheme, implemented in the ECLand model, was analyzed globally on hundreds of catchments. ERA5-forced reanalysis simulations of ECLand were coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…As pointed out by previous studies (e.g., Jacobi et al., 2015), a single‐layer snow model scheme is not capable to adequately represent the energy budget and the temperature profile in a snow pack. It has been found that such schemes are inferior in describing the evolution of the snowpack and some hydrological processes compared to snow schemes with multiple layers (e.g., Zsoter et al., 2022). Furthermore, the ability to create an aerosol stratification, which describes the vertical distribution of the aerosols in snow, is not possible when having only one single layer.…”
Section: Methodsmentioning
confidence: 99%
“…As pointed out by previous studies (e.g., Jacobi et al., 2015), a single‐layer snow model scheme is not capable to adequately represent the energy budget and the temperature profile in a snow pack. It has been found that such schemes are inferior in describing the evolution of the snowpack and some hydrological processes compared to snow schemes with multiple layers (e.g., Zsoter et al., 2022). Furthermore, the ability to create an aerosol stratification, which describes the vertical distribution of the aerosols in snow, is not possible when having only one single layer.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst complex representation of snow processes through multiple snow layers was shown to improve both snow characteristics (depth and mass) and 2 m temperature compared to a single layer modelling in ecLand (Arduini et al, 2019), the evaluation was limited to nine super sites with in‐situ snow and soil temperature observation datasets. Zsótér et al (2022) extended the evaluation to river discharge at 453 locations with daily observed timeseries of at least 8 years of good quality data in snow‐impacted regions (defined as with a snow to rainfall ratio of at least 10%). By also comparing river discharge and hydrological‐related variables such as snow melt, surface and subsurface runoff from a hydrological reanalysis configuration using 11 different snow module parameterizations within the ecLand land surface scheme and the CaMaFlood river routing (Yamazaki et al, 2011), they were able to diagnose errors introduced in the multi‐layer snow‐scheme (Figure 11) and identify a parameterization avoiding a degradation in the land hydrological processes.…”
Section: Examples Of Applications Of Global Hydrological Reanalysismentioning
confidence: 99%
“…All water related variables are displayed as catchment totals in order to compare them directly to river discharge (please note the values are divided by 1000 for river discharge, snowmelt and subsurface runoff). Each coloured line is associated with a snow‐scheme parameterization, with river discharge observations shown in dashed black line—for simplicity, the experiment characteristics are not explained here but can be found in Zsótér et al (2022).…”
Section: Examples Of Applications Of Global Hydrological Reanalysismentioning
confidence: 99%
“…The new scheme dynamically varies the number of snow model layers depending on the snow depth and provides snow temperature, density, liquid water content and albedo as prognostic variables. In addition, snow and frozen soil parameters were modified for improved river discharge (Zsoter et al, 2022) and permafrost extent (Cao et al 2022). An additional upgrade in nextGEMS Cycle 3 was a package of changes to ECLand which will be included in the next operational IFS cycle (49R1).…”
Section: Km-scale Surface Processesmentioning
confidence: 99%